CHALLENGES OF FEMALE PRINCIPALS IN MADRASAH LEADERSHIP IN BANDA ACEH: A GENDER ANALYSIS - Sakdiah, Sakdiah; Srimulyani, Eka; Gade, Syabuddin; Akmal, Saiful; Furqan, Muhammad (Universitas Islam Negeri Ar-Raniry, 2024)
Women's leadership is gaining more recognition in the public eye, particularly in professional leadership roles within educational institutions. Despite facing challenges such as seniority, local customs, and societal perceptions, these obstacles do not deter women from their leadership roles in educational institutions. In fact, they strive to create better opportunities for future leadership. The challenges faced by female school principals are often influenced by the prevailing patriarchal culture in society and community life. This research employs a qualitative method with a gender analysis approach. The findings reveal that challenges related to seniority and local customs are dominant issues for female school principals in Aceh. Seniority comes into play when younger school principals are perceived as inexperienced leaders by their senior counterparts, even if they possess the necessary competencies for the role. On the other hand, local customs are influenced by the presence of teachers who are local residents in the school. Additionally, dealing with policy dualism in private schools and collaboration with committees presents straightforward challenges for school principals, influenced by the research location, student backgrounds, and school status. The strategies offered by school principals involve continuous engagement, fostering better collaboration, and early consultation with relevant stakeholders. These efforts have helped ease tensions and lead to more effective solutions for overcoming these challenges.